(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate predictive factors of severe respiratory acidosis in patients receiving high-flow nasal oxygen during apnea in endoscopic vocal cord surgery. Subject and method: From October 2022 to December 2025, a prospective descriptive study was conducted at 108 Military Central Hospital. A total of 130 patients aged 25–77 years undergoing endoscopic vocal cord surgery were enrolled. All patients received high-flow nasal oxygen (HFNC) at a flow rate of 40–70 L/min, intravenous general anesthesia, complete neuromuscular blockade, and no mechanical ventilation during surgery. Demographic characteristics, airway assessment, apnea duration, and arterial blood gas parameters were recorded. Univariate and multivariate logistic regression analyses were performed to identify predictive factors of severe respiratory acidosis at the end of surgery. Results: At the end of surgery, 7 patients (5.4%) developed severe acute respiratory acidosis beyond the predefined threshold. In univariate analysis, apnea duration and Mallampati classification were identified as predictive factors for severe respiratory acidosis. However, in multivariate logistic regression analysis, apnea duration was the only independent predictive factor. Each additional minute of apnea increased the risk of severe respiratory acidosis at the end of surgery by 30.6%. Conclusion: Apnea duration is the sole independent predictive factor of severe respiratory acidosis in patients receiving high-flow nasal oxygen during apnea in endoscopic vocal cord surgery.